An Analysis of the compliance on PAS 41 of selected agricultural businesses in Pililla, Rizal - Alvaro, Gene Albert S.; Fiesta, Jhodie Anne S.; Mercado, Jao Renzo L.; Peleo, Rhamjel Joseph P.; Tan, Alena Xandra A. and Veloso, Jan Ira Minco S. 4 0 16; 5
NO ABSTRACT.
Undergraduate Thesis: (Bachelor of Science in Accountancy)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2